IMPLEMENTASI ASAS LEX SPECIALIS DEROGAT LEGI GENERALI DALAM SISTEM PERADILAN PIDANA - Shinta Agustina (Faculty of Law, Universitas Diponegoro, 2015)
This study aims to assess and analyze the application of the principle of lex specialis the derogat legi generali in the Criminal Justice System related to the stages in the criminal justice process, and the form of the indictment in applying the principle of lex specialis the derogat legi generali. The method used is empirical juridical with descriptive analytical. The result shows that this principle is applied in criminal cases that violating the general and special criminal provisions in the Penal Code, the general criminal provisions in the Penal Code and special criminal provisions outside the Penal Code, as well as criminal cases that violating two special criminal acts outside the Penal Code. Regarding the fase of criminal procedure in handling the case under this principle, it is implemented in the adjudication process, using the subsidiarity or cumulative model of chargingPenelitian ini bertujuan untuk mengkaji dan menganalisis penerapan asas lex specialis derogat legi generali dalam Sistem Peradilan Pidana terkait dengan tahapan dalam proses peradilan pidana, dan bentuk surat dakwaan dalam menerapkan asas lex xpecialis derogat legi generali tersebut. Metode penelitian yang digunakan adalah metode yuridis empiris yang bersifat deskriptif analitis. Hasil penelitian memperlihatkan bahwa asas lex specialis derogat legi generali diterapkan dalam perkara pidana yang mempertemukan ketentuan pidana umum dan khusus dalam KUHP, ketentuan pidana umum dalam KUHP dan ketentuan pidana khusus di luar KUHP, serta perkara pidana yang mempertemukan dua atau lebih ketentuan pidana khusus di luar KUHP. Berkenaan dengan tahapan dalam sistem peradilan pidana, asas ini diterapkan dalam tahap adjudication, yang mengharuskan surat dakwaan dibuat dalam model subsidiaritas atau kumulatif